Regional Patterns of Structural Green Infrastructure and Landscape Diversity: Implications for Sustainable Development in Europe - Mempel-Śnieżyk, Anna; Pluta, Agata; Girul, Agata (Publishing House of Wroclaw University of Economics and Business, 2025)
The aim of this study was to identify and compare regional differences in structural green infrastructure (SGI) and landscape diversity (SHDI) across European NUTS2 regions. The research focused on identifying disparities within and between regions, presenting projected SGI changes by 2050, and highlighting the relevance of these patterns and trends for sustainable development planning. The study used data from the LUISA model and GIS tools to present the distribution of SGI and SHDI in 2020 and the expected dynamics of change. Statistical methods, including coefficients of variation and box plots, were applied to illustrate the distribution of values and to indicate regions with particularly high or low SGI shares. The results reveal significant differences between regions and highlight the persistence of areas with low SGI levels in future projections. These findings underline the need for regional policies tailored to territorial specificities to better support green infrastructure development and contribute to achieving the goals of the European Green Deal and the EU Biodiversity Strategy.
Quote as: Mempel-Śnieżyk, A., Pluta, A., & Girul, A. (2025). Regional Patterns of Structural Green Infrastructure and Landscape Diversity: Implications for Sustainable Development in Europe. In B. Drelich-‑Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 63-74). Publishing House of Wroclaw University of Economics and Business.
Keywords: green infrastructure; landscape diversity; regional disparities; sustainable development; LUISA model; GIS spatial analysis